An Active‐Oxygen‐Scavenging Oriented Cathode‐Electrolyte‐Interphase for Long‐Life Lithium‐Rich Cathode Materials. Issue 7 (4th December 2021) - Wang, Yajing; Cai, Senrong; Sun, Zongqiang; Hou, Qing; Huang, Haihong; Cheng, Jiancong; Fan, Jingmin; Zheng, Mingsen; Dong, Quanfeng
Abstract: Lithium‐rich layered oxides with high energy density are promising cathode materials, thus having attracted a large number of researchers. However, the materials cannot be commercialized for application so far. The crucial problem is the releasing of lattice oxygen at high voltage and resulting consequence, such as decomposition of electrolyte, irreversible phase transition of crystal structure, capacity degradation, and voltage decay. Therefore, capturing active‐oxygen and further constructing a cathode‐electrolyte‐interface (CEI) protective layer via the scavenging effects should be a fundamental step to solve these issues. Herein, β‐carotene with antioxidant properties is used as a scavenging molecule to achieve this goal. The control of active oxygen species effectively alleviates the decomposition of carbonate electrolyte under high voltage. The introduction of β‐carotene additives can also be adjusted in situ to generate a customized CEI film, which is a double‐layer structure with external organic components and internal inorganic components. Moreover, the β‐carotene‐containing electrolyte system exhibits better thermal stability. Benefited from these, Lithium‐rich cathode of β‐carotene‐containing electrolyte shows outstanding long‐life cycle stability, with 93.4% capacity retention rate after 200 cycles at 1 C; this electrochemical stability is superior to other electrolyte additive systems reported at present. Abstract : β‐carotene is introduced as a scavenging molecule to scavenge active‐oxygen species and form a high‐quality double‐layer cathode‐electrolyte interphase in situ, which effectively reduces the decomposition of electrolyte under high voltage and maintains the stability of crystal structure. Therefore, the capacity decay and voltage drop of the lithium‐rich cathode are effectively alleviated.